High expression of crystallin αB represents an independent molecular marker for unfavourable ovarian cancer patient outcome and impairs TRAIL‐ and cisplatin‐induced apoptosis in human ovarian cancer cells. Issue 12 (27th December 2012) - Volkmann, Juliane; Reuning, Ute; Rudelius, Martina; Häfner, Norman; Schuster, Tibor; v. Rose, Aaron Becker; Weimer, Joerg; Hilpert, Felix; Kiechle, Marion; Dürst, Matthias; Arnold, Norbert; Schmalfeldt, Barbara; et al.
Abstract: Dysregulated apoptotic pathways are regarded as major reasons for chemoresistance development as a particular challenge in ovarian cancer therapy. In search of molecular factors affecting human ovarian cancer cell apoptosis and, consequently, patient survival, we examined tumors of 103 platinum‐/taxane‐treated ovarian cancer patients by mRNA‐array hybridization, qPCR, and immunohistochemistry. We identified high expression of crystallin αB (CRYAB), a proposed negative regulator of tumor necrosis factor‐related apoptosis inducing ligand (TRAIL)‐mediated apoptosis. By Kaplan Meier analysis, this factor turned out to be significantly associated with poor patient outcome [overall survival (OS) p = 0.001, recurrence‐free survival (RFS) p = 0.003]. Elevated hazard ratios (HR) were estimated with regard to OS (HR = 2.11, 95% CI 1.10–4.06) and RFS (HR = 1.92, 95% CI 1.07–3.47) in multivariable analyses. These associations were confirmed in independent, publicly available mRNA data comprising 431 patients for OS ( p < 0.001) and 413 for RFS ( p < 0.001). Our findings were validated by studying apoptotic events in cultured human ovarian cancer cells which were stably transfected to express elevated CRYAB levels. These data emphasized the crucial role of CRYAB in human ovarian cancer biology since TRAIL‐ as well as cisplatin‐induced apoptosis was significantly impaired as a function of enhanced CRYAB expression. Taken together, we identified CRYAB as an independent biomarker for unfavourable outcome of human ovarian cancer patients. Since TRAIL is currently tested as anti‐cancer drug and large proportions of the present patient cohort displayed low CRYAB levels in their tumors, CRYAB may enable the selection of patient subgroups benefiting most from TRAIL‐containing therapy. Abstract : The development of chemotherapeutic resistance is thought to be driven largely by the dysregulation of apoptotic pathways, which promotes the survival of tumor cells. As a result, the selection of effective treatments for patients is facilitated by knowledge of the molecular factors that mediate resistance. That knowledge base is expanded here, by the discovery that elevated expression of the heat shock protein crystallin αB (CRYAB) may impair TRAIL‐ and cisplatin‐induced apoptosis in ovarian tumors. The findings indicate that CRYAB could serve not only to identify patients with the highest probability of responding to certain treatments but also as a prognostic biomarker for ovarian cancer.